2018
DOI: 10.1016/j.dental.2017.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different sterilization methods on surface characteristics and biofilm formation on zirconia in vitro

Abstract: It is evident that various sterilization methods could change the surface which contribute to different biofilm formation and colour on zirconia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 58 publications
(68 reference statements)
8
25
0
Order By: Relevance
“…The wettability of 3Y-TZP was also significantly changed by the treatments. When not subjected to autoclaving, the polished surface of 3Y-TZP was hydrophobic as previously reported [ 11 , 46 ], irrespective of whether ultrasonic scaling was performed (contact angle: approximately 70°). In contrast, the surface affected by LTD was hydrophilic (contact angle: approximately 28°), and additional ultrasonic scaling using a steel scaler tip returned the wettability from hydrophilic to hydrophobic.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The wettability of 3Y-TZP was also significantly changed by the treatments. When not subjected to autoclaving, the polished surface of 3Y-TZP was hydrophobic as previously reported [ 11 , 46 ], irrespective of whether ultrasonic scaling was performed (contact angle: approximately 70°). In contrast, the surface affected by LTD was hydrophilic (contact angle: approximately 28°), and additional ultrasonic scaling using a steel scaler tip returned the wettability from hydrophilic to hydrophobic.…”
Section: Discussionsupporting
confidence: 76%
“…The surface properties (e.g. surface roughness, surface free energy, and chemical conditions of the topmost surface) of zirconia play an important role in achieving appropriate biocompatibility and in reducing bacterial adhesion [ 10 , 11 ]. Ultrasonic scaling may mechanically alter the surface properties.…”
Section: Introductionmentioning
confidence: 99%
“…e reduction of the density of CH 3 groups compared to the hydroxyl groups has an important influence by increasing the hydrophilic behavior [17] of the sterilized hybrid coatings. Similar results were published by Wittenburg et al [36] and Han et al [37] when glass and zirconia surfaces were sterilized using similar processes. e highest contact angle values were found for the autoclaved samples, followed by the samples sterilized with ethylene oxide, and hydrogen peroxide plasma.…”
Section: Teos/mtes (24 H)supporting
confidence: 88%
“…Several surface modifications have been conducted on zirconia to modify surface roughness to promote cell attachment, e.g. grit blasting ("sand blasting") [39][40] , sterilization 41) , and hydrofluoric acid etching 39,42,43) . It was found that grit blasting can improve the mechanical properties of bioactive glass infiltrated zirconia with better osteoblast cell response 44) .…”
Section: Grit Blastingmentioning
confidence: 99%